Health promotion in nursing practice - Pender, Nola J. (Appleton & Lange, 1987)
A handy reference for health promotion frameworks, strategies and tools, this classic book focuses on national health promotion priorities identified in Healthy People 2010 - with special emphasis on culturally and racially diverse populations. The new edition of this text will expand upon the vision of the two new co-authors incorporated in the last edition. It will continue to be theory based but will include more application of health promotion. New information will be integrated on health promotion in the learning disabled and the use of herbal medicine as it relates to health promotion. There will be new case studies and reflective practice activities to apply student's knowledge. For nursing students as well as nurse practitioners, community health nurses, occupational health nurses, and school nurses.